Die for growing gallium oxide single crystal by edge-defined film-fed growth method - WANG XIN; ZHANG XINGZI; ZHENG DONG (2024)
The utility model relates to the technical field of gallium oxide single crystal growth, and discloses a mold for growing gallium oxide single crystals by an edge-defined film-fed growth method, a first siphon chamfer is arranged at the bottom of a slit surface of a first guide template, a plurality of groups of first siphon row holes are arranged on the lower half plate surface of the first guide template, and a plurality of groups of second siphon row holes are arranged on the lower half plate surface of the first guide template. A second siphon chamfer is arranged at the bottom of the slit surface of the second guide template; and a plurality of groups of second siphon row holes are formed in the lower half plate surface of the second guide template. According to the utility model, the size of a melt liquid supply opening at the bottom of the mold can be increased by utilizing the two groups of siphon chamfers in the form of edges and corners, full climbing of the melt is facilitated, and a conduction stat